PEB-COVID-19: Analysis of Students Behavior and ILMIZI Model in Environmental Learning - Ilmi Zajuli Ichsan; Henita Rahmayanti; Agung Purwanto; Diana Vivanti Sigit; Md. Mehadi Rahman (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2020)
Environmental learning during COVID-19 experienced a change to e-learning. The use of learning models must be compatible; one model that can be chosen was the ILMIZI model. In addition to learning the concept of COVID-19, students must also be able to implement it in the form of Pro-Environmental Behavior (PEB) COVID- 19. The purpose of this study was to analyze descriptively about PEB-COVID-19 and also analyze the potential of ILMIZI to be applied in e-learning. The research conducted using a descriptive method. The sample was 148 Junior High School students located in Bekasi City and Bandung city. The data was collected online using Google form. The results showed that the PEB-COVID-19 student score was already in the very high category. While the results of the analysis show that the ILMIZI model allows it to be used in e-learning. This study concluded that the score of PEB-COVID-19 students was still in the very low category and the use of the ILMIZI model was one form of learning innovation. Keywords: COVID-19, ILMIZI Model, PEB-COVID-19, Pro-Environmental Behavior